POTENSI BIOLOGI BIJI PEPAYA (Carica papaya L.) DALAM UPAYA PENINGKATAN KINERJA ITIK RAJA - Rini Rachmatika; Siti Nuramaliati Prijono (Buletin Peternakan, 2015)
This experiment was conducted to evaluate the effect of papaya seed in feed on Raja duck’s performance. Experimental animals were 72 birds of 7 days old Raja ducks. Variables observed were feed intake, body weight gain, and feed conversion ratio. Experiment was assigned in one way of Completely Randomized Design with four treatments and three replication (six birds each). The treatments diets were T0 = basal diets without papaya seed, T1=0.3%, T2=0.6%, and T3=1.2% papaya seed. Dietary treatment were provided until 45 days of age. Data were subjected to analysis of variance using SPSS 16.0 and continued with Duncan's Multiple Range Test for all significant results at 5% level of probability. Result showed that feeding diets with 1.2% papaya seed supplementation reduced feed intake but increased body weight gain, resulted in better feed conversion ratio (P<0.05). It might indicate that papaya seed has potency to improve performance of Raja ducks.(Key words: Duck, Feed conversion ratio, Papaya seed, Performance)